A Comparative Metabolomic Analysis Reveals Difference Manufacture Suitability in “Yinghong 9” and “Huangyu” Teas (Camellia sinensis) - Mei, Xin; Lin, Chuyuan; Wan, Shihua; Chen, Baoyi; Wu, Hualing; Zhang, Lingyun (Frontiers in Plant Science, 2021)
“Yinghong 9” is a widely cultivated large-leaf variety in South China, and the black tea made from it has a high aroma and strong sweet flavor. “Huangyu” is a light-sensitive tea variety with yellow leaves. It was cultivated from the bud-mutation of “Yinghong 9” and has a very low level of chlorophyll during young shoot development. Due to chlorophyll being involved in carbon fixation and assimilation, the changes in photosynthesis might potentially affect the accumulation of flavor metabolites, as well as the quality of “Huangyu” tea. Although “Huangyu” has a golden yellow color and high amino acid content, the mechanism underlying the formation of leaf color and drinking value remains unclear. The widely targeted metabolomics and GC-MS analysis were performed to reveal the differences of key metabolites in fresh and fermented leaves between “Yinghong 9” and “Huangyu.” The results showed that tea polyphenols, total chlorophyll, and carotenoids were more abundant in “Yinghong 9.” Targeted metabolomics analysis indicated that kaempferol-3-glycoside was more abundant in “Yinghong 9,” while “Huangyu” had a higher ratio of kaempferol-3-glucoside to kaempferol-3-galactoside. Compared with “Yinghong 9” fresh leaves, the contents of zeaxanthin and zeaxanthin palmitate were significantly higher in “Huangyu.” The contents of α-farnesene, β-cyclocitral, nerolidol, and trans-geranylacetone, which were from carotenoid degradation and involved in flowery-fruity-like flavor in “Huangyu” fermented leaves, were higher than those of “Yinghong 9.” Our results indicated that “Huangyu” was suitable for manufacturing non-fermented tea because of its yellow leaf and flowery-fruity-like compounds from carotenoid degradation.